2019
DOI: 10.1093/aje/kwz091
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Zika Virus Transmission Within Households During an Outbreak in Martinique, 2015–2016

Abstract: Since 2015, Zika virus (ZIKV) has caused large epidemics in the Americas. Households are natural targets for control interventions, but quantification of the contribution of household transmission to overall spread is needed to guide policy. We developed a modeling framework to evaluate this contribution and key epidemic features of the ZIKV epidemic in Martinique in 2015–2016 from the joint analysis of a household transmission study (n = 68 households), a study among symptomatic pregnant women (n = 281), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
1
9
2
Order By: Relevance
“…In contrast to our analysis, studies from other islands found substantially higher seroprevalence estimates, including 73% in Yap in 2007 [ 5 ], 49% in French Polynesia in 2013–2014 [ 10 ], and 42%–50% in Martinique in 2015 [ 7 , 31 ]. The differences in the estimated underlying infection burdens may be in part due to heterogeneity in exposure to infection even within an island population, as seen in early dengue serosurveys in Puerto Rico and municipality-level estimates for ZIKV infection rates [ 27 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our analysis, studies from other islands found substantially higher seroprevalence estimates, including 73% in Yap in 2007 [ 5 ], 49% in French Polynesia in 2013–2014 [ 10 ], and 42%–50% in Martinique in 2015 [ 7 , 31 ]. The differences in the estimated underlying infection burdens may be in part due to heterogeneity in exposure to infection even within an island population, as seen in early dengue serosurveys in Puerto Rico and municipality-level estimates for ZIKV infection rates [ 27 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our analysis, studies from other islands found substantially higher seroprevalence estimates, including 73% in Yap in 2007 (5), 49% in French Polynesia in 2013–2014 (10), and 42%–50% in Martinique in 2015 (7,34). The differences in the estimated underlying infection burdens may be in part due to heterogeneity in exposure to infection even within an island population, as seen in early dengue serosurveys in Puerto Rico and municipality-level estimates for ZIKV infection rates (33).…”
Section: Discussioncontrasting
confidence: 99%
“…During the ZIKV epidemic, a household-based cluster investigation of 367 participants from 19 clusters found that ZIKV seroprevalence ranged from 0-57% (4). An estimate based on blood donors alone was 21% (95% confidence interval: 18-24%) (32) while an integrated approach similar to ours estimated an infection rate of 32% (95% CrI: 29-35%) (33).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our findings are generally congruent with other studies aiming to understand arboviral epidemics. For example, it was estimated that within-household transmission only accounted for 22% of all ZIKV infections detected during an outbreak in Martinique in 2016, using data collected from a household transmission study, blood-donor seroprevalence studies, and laboratory-testing results among pregnant women with Zika-like illness [32] . Spatiotemporal modelling of data collected from the 2008-2009 dengue epidemic in Cairns, Australia, suggested that more than 50% of potential exposure locations were non-residential [33] .…”
Section: Discussionmentioning
confidence: 99%